Developmental Biology of Cardiochiles nigricollis Cameron a Larval Endo-parasitoid of Rice Leaffolders - Behera, K. S. (Recent Research Advances in Biology Vol. 10, 2021)
Cardiochiles nigricollis Cameron is a larval endo-parasitoid of the two rice leaf folder species, Cnaphalocrocis medinalis (Guenee) and Marasmia exigua Butler. Developmental biology of C. nigricollis was studied on the host C. medinalis. Usually third and fourth instar larvae of the leaffolder species were parasitized by the parasitoid. During the development of the parasitoid, four instars were discovered. The larvae of the first instar are segmented and slightly bent. Segmentation appeared in the second instar, and the tracheal system could be seen faintly. The head was clearly defined in the third instar, and the larva expanded in size. The full-grown larva emerged from the host six to eight days after the egg was laid. Females had a 5.3-day pupal period and males had a 6.7-day pupal period on average. Incubation time, larval time, and pupal time were all 1.2 days, 10 days, and 6.7 days, respectively. C. nigricollis went into diapause at the pupal stage, which began in late August and grew gradually until the first week of December, when the entire population went into diapause. This phenomena was only noticed during the rainy season. Males emerged after 213 days on average, and females after 224 days from diapausing pupae. The steady increase in the number of C. nigricollis entering diapause in the field population could be attributed to the presence of a heterogeneous population of C. nigricollis in the field that responded to changes in air temperature over time. Brachymeria sp., Orgilus sp., Trichomalopsis (Eupteromalus) parnarae Gahan and Elasmus sp. were reared as hyper-parasitoids on pupae of C. nigricollis.